SARS-COV-2 viroporins activate the NLRP3-inflammasome by the mitochondrial permeability transition pore - Guarnieri, Joseph W.; Angelin, Alessia; Murdock, Deborah G.; Schaefer, Patrick; Portluri, Prasanth; Lie, Timothy; Huang, Jessica; Wallace, Douglas C. (Frontiers in Immunology, 2023)
Background Compared to healthy controls, severe COVID19 patients display increased levels of activated NLRP3-inflammasome (NLRP3-I) and interleukin (IL)-1β. SARS-CoV-2 encodes viroporin proteins E and Orf3a(2-E+2-3a) with homologs to SARS-CoV-1, 1-E+1-3a, which elevate NLRP3-I activation; by an unknown mechanism. Thus, we investigated how 2-E+2-3a activates the NLRP3-I to better understand the pathophysiology of severe COVID-19. Methods We generated a polycistronic expression-vector co-expressing 2-E+2-3a from a single transcript. To elucidate how 2-E+2-3a activates the NLRP3-I, we reconstituted the NLRP3-I in 293T cells and used THP1-derived macrophages to monitor the secretion of mature IL-1β. Mitochondrial physiology was assessed using fluorescent microscopy and plate reader assays, and the release of mitochondrial DNA (mtDNA) was detected from cytosolic-enriched fractions using Real-Time PCR. Results Expression of 2-E+2-3a in 293T cells increased cytosolic Ca++ and elevated mitochondrial Ca++, taken up through the MCUi11-sensitive mitochondrial calcium uniporter. Increased mitochondrial Ca++ stimulated NADH, mitochondrial reactive oxygen species (mROS) production and the release of mtDNA into the cytosol. Expression of 2-E+2-3a in NLRP3-I reconstituted 293T cells and THP1-derived macrophages displayed increased secretion of IL-1β. Increasing mitochondrial antioxidant defenses via treatment with MnTBAP or genetic expression of mCAT abolished 2-E+2-3a elevation of mROS, cytosolic mtDNA levels, and secretion of NLRP3-activated-IL-1β. The 2-E+2-3a-induced release of mtDNA and the secretion of NLRP3-activated-IL-1β were absent in cells lacking mtDNA and blocked in cells treated with the mitochondrial-permeability-pore(mtPTP)-specific inhibitor NIM811. Conclusion Our findings revealed that mROS activates the release of mitochondrial DNA via the NIM811-sensitive mitochondrial-permeability-pore(mtPTP), activating the inflammasome. Hence, interventions targeting mROS and the mtPTP may mitigate the severity of COVID-19 cytokine storms.